UICC International Session: What are the implications of sharing the concept of Universal Health Coverage for cancer in Asia?. Issue 4 (April 2016) - Akaza, Hideyuki; Roh, Jae Kyung; Hao, Xishan; Wibulpolprasert, Suwit; Nozaki, Shinjiro; Park, Eun‐Cheol; Fukuda, Takashi; Sonoda, Shigeto; Kawahara, Norie
Abstract : The Japan National Committee for the Union for International Cancer Control (UICC) and UICC – Asia Regional Office organized an international session as part of the 74th Annual Meeting of the Japanese Cancer Association on the topic "What are the implications of sharing the concept of Universal Health Coverage for cancer in Asia?" Universal Health Coverage (UHC) is included in the United Nations' Sustainable Development Goals and aims to ensure that all people can receive high‐quality medical services, are protected from public health risks, and are prevented from falling into poverty due to medical costs or loss of income arising from illness. The session discussed the growing cost of cancer and the challenges that this poses to the establishment and deployment of UHC in the Asian region, where countries face budgetary and other systemic constraints in tackling and controlling cancer. It was noted how sharing concepts on UHC will assist mutual learning among Asian countries and help in the formation of guidelines that can be adapted to national and regional realities. Presentations included a status report on UHC for cancer control in Thailand, and a report from the WHO Kobe Centre concerning prospects for collaborative research on UHC. Also discussed were the current status of cancer burden and control in China and Korea and Japan's progress in systemizing cost‐effectiveness evaluation. The final presentation highlighted the importance of gathering social and economic data across Asia in order to build a picture of commonalities and differences in the region. Abstract : The Japan National Committee for the Union for International Cancer Control (UICC) and UICC‐Asia Regional Office (ARO) organized an international session as part of the official program of the 74th Annual Meeting of the Japanese Cancer Association to discuss the topic "What are the implications of sharing the concept of Universal Health Coverage for cancer in Asia?" The presenters and participants discussed the growing cost of cancer in the Asian region and the challenges that this poses to the establishment and deployment of UHC in the countries of Asia, all of which face budgetary and other systemic constraints in tackling and controlling cancer in the region.